Yammer for Office 365 - Walsh, Heather; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"In this course, students will gain familiarity with the features and functionality of Yammer in Office 365. Students will overview the interface and features, navigate Yammer, edit a profile, work with and manage conversations, work with groups, and connect to an external network. Additionally, students will work with and manage messages, chat using Online Now, search Yammer, create polls, give praise, and make announcements."--Resource description page.
Title from resource description page (Safari, viewed August 26, 2016).
Publisher's name and date of publication from resource description page.
Presenter, Heather Walsh.
Keywords: Microsoft Office; Cloud computing; Electronic books